Holistic Exploration of Islamic Education in the Formation of Children's Character in the Family - Suud Sarim Karimullah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
This study strongly focuses on the holistic exploration of Islamic education in the context of forming children's character in the family environment. To explore a deeper understanding of the role of Islamic education in the shape of children's character, this study uses a literature study approach with integrative and comprehensive literature analysis. This approach is a solid foundation for understanding the theoretical and conceptual framework related to Islamic education in forming children's character in the family. The results of this study indicate that a holistic exploration of Islamic education has a significant impact on shaping the nature of children in the family. This holistic approach includes religious values, morality, and ethics, which significantly affect the development of the child's personality. As the primary exemplars and educators in the family, parents play a central role in conveying and applying these values to children. In addition, the influence of the formation of children's character in the family also involves conflict management, honesty, social responsibility, understanding of values, and problem-solving abilities. Therefore, parents' awareness of their essential role in guiding children towards solid character and good ethics is indispensable to creating a generation that contributes positively to society. A holistic approach in Islamic education, and the influential role of parents, can better shape the child's character in the family.